Effect of two different cropyear and the agrotechnological factors on the agronomic characteristic of the winter weat in a lon-term experiment - Vári, Enikő; Pepó, Péter (Acta Agraria Debreceniensis, 2012)
We studied the effects of crop rotation, fertilization and crop protection technologies on occurence of the major ear- and leaf-diseases (powdery mildew, helminthosporiosis, leaf rust, Fusarium wilt) and the degree of lodging in the winter wheat variety Mv Pálma in two very different years (2006/2007=dry; 2009/2010=rainy). The experiments were carried out at the Látókép Experimental Farm of the University of Debrecen CAAES in triculture (pea-wheat-maize) and biculture (wheat-maize) at five fertilization levels by applying three different crop protection technologies (extensive, average, intensive). In the cropyear of 2006/2007, the disease severity of leaf diseases was higher than the average in both crop rotations in spite of the fact that the weather during the whole vegetation period was dry. Infection by powdery mildew, helminthosporiosis and leaf rust increased with increasing fertilization, the highest infection was measured at the highest fertilization level (N200+PK) in the extensive crop protection technology. According to the results, no infection of ears by Fusarium and no lodging occurred in either bi- or triculture due to the dry year. The extremely rainy weather in 2009/2010 was favourable not only for the vegetative development of the stand, but also increased the occurance of leaf-, stalk- and ear-diseases and a high degree of lodging was observed. The highest infection by powdery mildew was observed in the plots with the highest fertilizer dosage under an extensive crop protection technology. A much higher helminthosporiosis infection was measured than in the cropyear of 2006/2007. The wet weather and higher than average temperature promoted the occurence and spreading of leaf rust. Under an extensive crop protection technology, a leaf rust infection of 24% and 31% was detected after maize and pea as a forecrop, respectively, in the N200+PK treatment. As opposed to 2006/2007, the disease severity of Fusarium was 3–8% and 2–7% in the control after maize and pea as a forecrop, respectively. This value, similarly to that of other pathogens, increased with increasing fertilization levels. Due to the large vegetative mass, a significant lodging was observed in the wheat stands in both bi- and triculture (17–100%, 12–100%).